Nesting of Buff-throated Saltator Saltator maximus (Thraupidae) with the first report of brood parasitism by Shiny Cowbird Molothrus bonariensis (Icteridae) - Arteaga-Chávez, William Andrés (Revista Ecuatoriana de Ornitología, 2023)
The Buff-throated Saltator Saltator maximus is common in open areas, second-growth vegetation, and borders from southern Mexico to southern Brazil. Although there is published information on its breeding biology, knowledge is still scarce. Here I describe two nesting events in northwestern Ecuador and present the first record of brood parasitism by Shiny Cowbird Molothrus bonariensis on S. maximus. I studied two nests in March–May 2020 and collected data on nest composition, dimensions, and daily eggs’ and nestlings’ weight. The nests were bulky cups, and the clutch consisted of two light blue eggs with black lines and scrawls on the larger pole. The incubation period was 14 days. The average rate of weight loss in the egg was 0.04 ± 0.01 g/day and the daily weight gain of the chicks was 1.87 g/day. In contrast, M. bonariensis chicks gained weight more rapidly (1.99 g/day). One nest was probably predated; chicks in the other nest died after being infested by Philornis sp. (Muscidae). I believe it is important to document nesting events in detail, which allows estimating the impact of brood parasitism and ectoparasites on reproductive success.
Keywords: Reproductive biology, host, eggs, brood parasitism, Philornis